Pelestarian Budaya Adat Melayu Jambi dalam Era Pembangunan - Rosdiana, Ike; Sawitri, Adelia Ajeng; Ifsya, Radha; Syamsiah, Syamsiah; Mustiah, Mustiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The customs and culture of Jambi play a vital role in shaping the norms and values of the local community, serving as a foundation for their identity. However, modernization and developments such as the expansion of palm oil plantations pose significant challenges to cultural preservation. This study aims to examine the impact of development on Jambi's customs and culture, including Malay traditions, Seloko customs, and the potential of traditional houses as cultural tourism destinations. The research adopts a literature review method, analyzing relevant academic sources. The findings reveal cultural value losses alongside opportunities to preserve traditions through multicultural approaches and the strengthening of Jambi’s community character. In conclusion, strategic steps are essential to protect and develop Jambi’s customs to remain relevant in the modern era.